Irenologia e polemologia. Due concetti imprescindibili dalla cultura della pace - Nodari, Paulo César (Filosofia, 2023)
The objective of this article is to present the thesis that peace and violence cannot be treated as if they were natural human characteristics. The naturalization of peace our violence can bring some vices and sociocultural, educational and political damages that are at least very dangerous for everyone regarding the understanding of the lives of human beings and all other beings in the world. This article aims to support the thesis that the culture of peace does not come fortuitously and does not come about suddenly or from one moment to another, demanding, precisely for this reason, constant, continuous and permanent commitment and efforts from ereryone, because violence, even if it is a possibility, is always on the verge of breaking out in many and diverse forms of manifestation. In this sense, we seek to develop the reflection of this article in two moments. Initially, we seek to analyze two important concepts of the culture of peace, namely, “irenology” and “polemology”, in order to, in a second moment, reflect and present the essencial task of education for the culture of peace at all levels of education, be it personal, community, and also institutional. Finally, it points to the key idea that each human being as a citizen of the world needs to feel and become a potencial educator, na artisan and a guardian of peace.